2008
DOI: 10.3346/jkms.2008.23.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Severity of Obstructive Sleep Apnea and Heart Rate Variability Indices

Abstract: The risk of cardiovascular disease is known to be increased in obstructive sleep apnea syndrome (OSAS). Its mechanism can be explained by the observation that the sympathetic tone increases due to repetitive apneas accompanied by hypoxias and arousals during sleep. Heart rate variability (HRV) representing cardiac autonomic function is mediated by respiratory sinus arrhythmia, baroreflex-related fluctuation, and thermoregulation-related fluctuation. We evaluated the heart rate variability of OSAS patients duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
62
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 27 publications
(28 reference statements)
15
62
0
3
Order By: Relevance
“…It indicated that nuLF and LF/HF ratio were greater in OSA patients and nuHF was lower in OSA patients. These results are consistent with findings of previous studies [5,16,17,34]. They found that the increased LF power and LF/HF ratio in OSA patients, and the greater the AHI of OSA patient, the greater the LF/HF ratio [5,16,17,34].…”
Section: Comparison With Other Worksupporting
confidence: 83%
See 1 more Smart Citation
“…It indicated that nuLF and LF/HF ratio were greater in OSA patients and nuHF was lower in OSA patients. These results are consistent with findings of previous studies [5,16,17,34]. They found that the increased LF power and LF/HF ratio in OSA patients, and the greater the AHI of OSA patient, the greater the LF/HF ratio [5,16,17,34].…”
Section: Comparison With Other Worksupporting
confidence: 83%
“…Gong et al [16] used 25 OSA patients and 27 normal participants and found that the LF/HF and normalized LF (nuLF) were significantly associated with the value of AHI. Gula et al [9] and Park et al [17] demonstrated that patients with more severe OSA exhibited a higher LF/HF which represents the balance between the sympathetic and parasympathetic systems. The experiment by Pan et al [5] was performed on 10 mild OSA patients, 24 moderate OSA patients, 45 severe OSA patients, and 10 normal participants.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the HRV indexes have been used to understand various conditions, such as coronary artery disease [54][55][56][57], cardiomyopathy [26.58], arterial hypertension [29,[59][60][61], myocardial infarction [62][63][64], sudden death [65], chronic obstructive pulmonary disease [2,66,67], renal failure [68], heart failure [69], diabetes [70], stroke [71], Alzheimer's disease [72] leukemia [73], obstructive sleep apnea [74], epilepsy [75], headache [76], among others.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…This finding is in agreement with the findings of other researchers. Park et al also found that these values were higher in patients with severe OSAS when compared to moderate OSAS and they concluded that the frequency-domain indices of heart rate variability revealed the difference between the groups better 13 . Noda et al found that circadian rhythms of the LF, HF, and LF/HF ratio differed significantly in patients with severe OSAS when compared with those with mild OSAS and controls 11 .…”
Section: Discussionmentioning
confidence: 95%
“…They also found that the LF: HF ratio (which represents sympatho-vagal balance), was higher in patients with moderate OSAS compared to controls and patients with severe OSAS 12 . The LF/HF ratio and mean powers of low frequency (LF), very low frequency (VLF) and total frequency (TF) were found to be higher in patients with severe OSAS when compared to moderate OSAS in a study by Park et al, and they concluded that the frequency-domain indices revealed the difference between the groups better than time-domain indices with the LF/HF ratio being the most useful parameter to estimate the Apnea Hypopnea index (AHI) in OSAS patients 13 .…”
Section: Introductionmentioning
confidence: 99%